Pengaruh Dukungan Sosial terhadap Motivasi Belajar Siswa Kelas XE-6 SMA N 1 Ngemplak Boyolali - Putri Wulansari (Universitas Maritim AMNI Semarang, 2025)
Achievement motivation is an important factor in achieving individual success, especially among teenagers. This research aims to explore the influence of social support from parents, teachers and peers on students' learning motivation at SMA N 1 Ngemplak, Boyolali. According to Santrock (2003), achievement motivation is the desire to complete tasks in order to achieve success. However, low levels of parental concern and conflict within the family often hinder students' learning motivation. Interviews with students show that many of them feel less supported, both at home and at school, which has a negative impact on their enthusiasm for learning. The research method uses a quantitative approach with a descriptive design, involving class XE-6 students and collecting data through questionnaires about social support and learning motivation. The research results show that there is no significant relationship between social support and learning motivation, with a p-value of 0.166, which is greater than the significance level of 0.05. Nevertheless, this research confirms the importance of environmental support to increase student learning motivation.